Condicionamento fisiológico e tolerância ao estresse salino em sementes de coentro (coriandrum sativum l.) - Dantas, Nadjamara Bandeira de Lima (Universidade Federal Rural do Semi-Árido, 2019)
The coriander (Coriandrum sativum L.) is widely cultivated in the Brazilian Northeast, mainly by family farming. However, the salinization of soils and water is one of the main environmental problems faced in this region, which may compromise the development of culture. In this sense, physiological conditioning may be a promising alternative to minimize such negative effects. Thus, the objective was to evaluate methods for the physiological conditioning in coriander seeds, and their effects on germination and vigor in salinity conditions. For this, three lots of coriander seeds, grow crops SF Verdão 177, were purchased and purchased locally. The study was divided in two stages. First, the initial quality of the lots was determined by determining the moisture content, first count, germination, seedling length, seedling dry mass, accelerated aging and electrical conductivity. The methods tested for conditioning were: hydro conditioning for 1, 2 and 3 days; the polyethylene glycol solution (PEG) in the concentrations of -0.2 and -0.4 MPa for 1, 2 and 3 days and the control. The experimental design was a completely randomized design with four replicates of 25 seeds. In the second step, the three batches were conditioned in PEG solution -0,2 MPa, for 1, 2 and 3 days at 20 ° C for lots B, C and A, respectively. Then, seeds conditioned and without conditioning were placed to germinate under salt stress at levels 2, 4, 6 and 8 dS.m-1 at 20-30 ° C. The experimental design was completely randomized, in a 2x4 factorial scheme (conditioned and unconditioned seeds and four salinity levels), with four replicates of 25 seeds. The variables analyzed were: first count, germination, seedling length and dry mass of seedlings. It has been found that osmoconditioning with PEG solution -0.2 MPa is beneficial to the performance of coriander seeds. However, the batches responded differently to the conditioning time, and the period of 1, 2 and 3 days for lots B, C and A, respectively, were recommended. The osmotic conditioning favored the germination and vigor of the seeds under salt stress
Keywords: Apiaceae; salinidade; priming; hortaliça; Apiaceae; salinity; priming; vegetable; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE